An internal integrated marketing communication approach for city branding - Mabula, Refilwe Marlene (University of the Free State, 2019)
The global competition amongst cities necessitates the need for cities to brand themselves. The practice of city branding is growing, with many cities pioneering unique ways to build their brands. City branding is becoming increasingly popular due to the numerous benefits that it holds for cities. The city of Kimberley has a rich history of diamond mining and the Big Hole is a popular tourist attraction in the city. Despite this strong brand asset, it appears that the strength of the city brand has deteriorated. The study sought to answer the research question: How can an internal integrated marketing communication approach be used to empower the tourism sector of Kimberley, and enhance the Kimberley city brand? For this study, one research question and primary research objective was set. The goal of this study was to provide guidelines for an internal integrated marketing communication approach for the tourism sector of Kimberley. To attain this goal, the following secondary objectives were set: to determine the nature and scope of city branding and brand equity; to give an overview of the importance of an internal focus in integrated marketing communication; and to investigate the knowledge and experiences of the role players in the tourism industry of Kimberley regarding the brand Kimberley. Considering the aim and objectives of the study, a qualitative approach was followed and a literature review and phenomenology were used as research strategies. The former was through a review of relevant literature on the main theoretical domains of the study and the latter through in-depth interviews to assess the knowledge of Kimberley’s key tourism role players about the city. Results suggested that there is lack of brand awareness of the Kimberley city brand and, amongst the internal stakeholders, the brand’s identity is not clear. They also suggest that the city has a poor internal brand image that evoked negative brand attitudes, making it difficult for the city to build brand equity and strengthen its brand to compete with other cities. The same results suggest that there is there is poor management of the brand internally. Feelings of disheartenment emerged due to the non-integrated marketing communications in the city that explained the lack of brand awareness in the city. The conclusions of the study indicated that there was a lack of internal collaborative partnerships amongst the role players to elevate the Kimberley brand due to the fact that the tourism sector did not operate as system. This also indicates that a lack of internal communications, internal branding and internal marketing in the city highlight its weak internal relationships. To address the identified challenges, participants suggested a number of interventions to improve the visual image of the city, by improving cleanliness and the city’s dilapidated infrastructure. Since the tourism sector is services based, participants believed that the Kimberley brand can be improved if employees are empowered through customer training. The need to build strategic partnerships to propel the vision of the city was also highlighted. Moreover, as a first step to address the issues raised, much needed attention needs to be paid to the physical appeal of the city. From these conclusions, recommendations were supplied based on the “4 p’s” of city brand management, namely, people, process, place and partnerships.It is anticipated that this study will assist internal stakeholders in Kimberley on how to improve the city branding strategies in an effort to enhance the image of city.
Dissertation (M.A. (Communication Science))--University of the Free State, 2019
Keywords: Branding; City branding; Brand equity; Integrated Marketing Communication; Internal branding; Internal marketing; Internal communication; Phenomenology